Structural adjustment, agriculture, and deforestation in the Sumatera regional economy - San, Nu Nu; Lofgren, Hans; Robinson, Sherman (International Food Policy Research Institute, 2000)
The Asian financial crisis led to a major devaluation of the Indonesian exchange rate, macro instability, and the need for a “structural adjustment” program. The real devaluation affects prices throughout the economy and has a major impact on growth, production, deforestation, and income distribution in the Sumatera region. This paper uses computable general equilibrium (CGE) models —a national model and a regional model of Sumatera— that focus on agriculture to explore the impact of a real devaluation on the economy of Sumatera. The model incorporates commodity and factor market linkages between Sumatera, the rest of Indonesia, and the world (through commodity trade). We analyze a possible policy response of imposing an export tax of 5-20 percent on processed wood to discourage further deforestation in the region. The results show that the proposed export tax reduces production of raw timber and processed wood, but at the cost of lowering exports and hence making the macro adjustment more difficult. Given the current situation, it is impossible to predict exactly how the resolution of the current macro crisis will unfold. We model two alternative macro adjustment scenarios that should bracket the likely response of the Sumatera region to the devaluation and structural adjustment program. In the first, we assume that regional investment is a proportion of regional aggregate income (or regional absorption), and that the adjustment burden is shared proportionately between aggregate consumption and investment. In the second, regional savings and investment are assumed to fall more, as the region’s trade balance is forced to improve dramatically to reflect the large required changes in the national trade balance.